A class Ⅰ lentogenic newcastle disease virus strain confers effective protection against the prevalent strains. (January 2020) - Li, Shu-yun; You, Guo-jin; Du, Ji-teng; Xia, Jing; Wen, Yi-ping; Huang, Xiao-bo; Zhao, Qing; Han, Xin-feng; Yan, Qi-gui; Wu, Rui; Cao, San-jie; Huang, Yong
Abstract: The traditional vaccine strains, such as LaSota, do not completely prevent the shedding of NDV. An ideal vaccine which could not only prevent the clinical signs, but significantly reduce the shedding of NDV is urgently needed for the eradication of ND. In this study, an NDV isolate APMV-1/Chicken/China (SC)/PT3/2016 (hereafter referred as PT3) was identified as a class Ⅰ NDV and a lentogenic strain. The antigenic relationship between PT3 and 3 other NDV strains, including vaccine strain LaSota and 2 prevalent genotype Ⅶd and Ⅵb strains were analyzed. The protective efficacy of PT3 and LaSota against challenge with genotype Ⅶd and Ⅵb strains were assessed. The antigenic analysis result showed that 4 strains belong to the single serotype and the PT3 antiserum exhibited the highest HI titer against 3 other NDV strains. The results of protective efficacy showed that both of LaSota and PT3 could provide 100% survivability for infected chickens. However, PT3 performed better in inducing higher humoral responses and reducing virus shedding than the LaSota strain. Lentogenic strains from Class I NDV appear to be promising vaccine candidates for the control of ND, and allows for the easy discrimination of field NDV and vaccine strains.